Platelet-Rich Plasma as a Potential New Strategy in the Endometrium Treatment in Assisted Reproductive Technology - Lin, Yunying; Qi, Jia; Sun, Yun (Frontiers in Endocrinology, 2021)
The success rate of assisted reproduction techniques (ART) has long been less than satisfactory albeit the great progress made in recent years, demonstrating the need for alternative options in the ART cycles. Growing evidence correlates the effect of intrauterine platelet-rich plasma (PRP) infusion on the endometrium with reassuring reproductive results. Thus, in this review, we focus on the current clinical and mechanical evidence on PRP and its effect on endometrial receptivity, and assess the features, benefits and limitations of the current studies and potential risks of PRP in ART.